UMPSA explores Pineapple Industry Collaboration with the Malaysian Pineapple Industry Board (LPNM) - Naqiah, Puaad (UMPSA, 2024)
PEKAN, 11 July 2024 - Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is exploring the pineapple industry through collaboration with the Malaysian Pineapple Industry Board (LPNM) with the signing of a memorandum of understanding (MoU) related to research, development, and technology empowerment in the pineapple industry in Malaysia.